2015
DOI: 10.1088/2040-8978/17/11/114013
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing gold nanostars as a colloid-based surface-enhanced Raman scattering (SERS) substrate

Abstract: The one-pot seedless protocol provides a facile approach in the synthesis of gold nanostars (AuNS) that involves only three reagents, gold (III) chloride (HAuCl 4 ), silver nitrate (AgNO 3 ) and ascorbic acid (C 6 H 8 O 6 ). While studies correlating the synthesis parameters of the seedmediated protocol to surface-enhance Raman scattering (SERS) enhancement is well reported, the same understanding of the one-pot seedless protocol is limited. Here, we aim to elucidate how the synthesis parameters of AuNS from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 41 publications
1
73
0
3
Order By: Relevance
“…In addition to the high efficiency of SERS effect on nanostar‐based substrates, they possess very good long‐term stability of SERS signal over time . Previously we have studied enhancement of Raman signals of R6G molecules using type I substrates; other authors studied SERS substrates with nanostars using other molecules …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the high efficiency of SERS effect on nanostar‐based substrates, they possess very good long‐term stability of SERS signal over time . Previously we have studied enhancement of Raman signals of R6G molecules using type I substrates; other authors studied SERS substrates with nanostars using other molecules …”
Section: Resultsmentioning
confidence: 99%
“…As will be shown below, both SERS mechanisms are working for the gold starlike NPs that were synthesized and characterized in the present study. There are many papers that analyze these objects, which is caused by the perspectives of their applications . However, there are still many unsolved problems in this field and the values of enhancement coefficients reported for similar SERS substrates and molecules differ by orders of magnitude .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak enhancement brought by Ag NSPs_0.05/tape is due to sufficient amounts of agglomeration that consequently results in optimized interspike distances. On the other hand, the decrease in peak intensities with increasing suspension concentration is due to heavy agglomeration that results in more radiation being scattered by the system, thus less laser energy is available to form "hot spots" [15][16][17]. In addition, it cannot be explicitly concluded that the enhancement comes from resonance effects brought by the laser wavelength and the LSPR of the substrate since the LSPR information was not investigated.…”
Section: Evaluation Of the Sers Effect Of Ag Nsps_x/tapementioning
confidence: 99%
“…Aside from the intra-spike gap, "hot spots" formed on a single Ag NSP, the clustering of these nanostructures also plays an important role in contributing to the SERS effect since the distance among the nanostructures is also critical in providing the enhancement of SERS signals. The agglomeration of Ag NSPs should be sufficient enough to create an effective density of "hot spots" in obtaining an optimized SERS enhancement [17]. Considering the effects of each signal contributing to single or overlapped multiple Ag NSPs, larger regions of high electrical field are created and, consequently, the overall effect of SERS are generated.…”
Section: Mechanism Of Sers Upon Ag Nsps_x/tapementioning
confidence: 99%